Adieu Rabenmutter: The effect of culture on fertility, female labour supply, the gender wage gap and childcare - Rainald Borck (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper studies the effect of cultural attitudes on childcare provision, fertility, female labour supply and the gender wage gap. Cross-country data show that fertility, female labour force participation and childcare are positively correlated with each other, while the gender wage gap seems to be negatively correlated with these variables. The paper presents a model with endogenous fertility, female labour supply and childcare choices which fits these facts. There may exist multiple equilibria: one with zero childcare provision, low fertility and female labour supply and high wage gap, and one with high childcare provision, high fertility and female labour supply and low wage gap.
Keywords: J13; J21; J16; 330; cultural preferences; fertility; female labour supply; wage gap; childcare; Soziale Werte; Kinderbetreuung; Fruchtbarkeit; Frauenerwerbstätigkeit; Lohndifferenzierung; Familienökonomik; Theorie; OECD-Staaten